A Long History of Wall Street Bailouts and How Puerto Rico Will Not Be Different. (1st July 2018) - Mayra Velez-Serrano
Abstract : Even though in 2012, publications such as Morningstar were advising investors to "Watch Out for Puerto Rico, " and pundits were commenting about a very likely default, by 2013 and 2014, Wall Street was frenetically buying up Puerto Rican bonds. Wall Street incurred in a risky behavior that is comparable with what happened during the 1980s Latin America crisis, the 1997 Asian crisis, the 1998 Long-Term Capital Management (LTCM) crisis, and the 2008 mortgage subprime crisis. By giving a brief overview of a series of economic crises around the world caused by speculation and risky lending, this article shows that the case of Puerto Rico, a nonincorporated territory of the United States of America, mirrors the same patterns of financialization of the economy and risky lending. It suggests that Wall Street bought these speculative-level bonds since this type of behavior has always been compensated by a bailout either through the US Treasury or an International Financial Institution (IFI), thus posing a moral hazard problem. The main argument of this article is that Wall Street and other bondholders will try to get their risky loans paid by the Government of Puerto Rico by forcing austerity measures, and when this inevitably fails, they will turn to the Treasury of United States to recover their money. It concludes with the question on how long the Island will have to suffer through the wave of higher taxes and cuts on social services before Washington bails them out.